مستوى تطبيق مبادئ الحكومة في الجامعات اليمنية: دراسة مقارنة بين الجامعات الخاصة والحكومية= The level of application of the governance principles in Yemeni Universities: a comparative study between private and government universities - Al-Hidabi, Dawood Abdulmalek Yahya; Al-Azizi, Mahmood Abdo Hasan (University of Science and Technology, Yemen, 2019)
The study aimed to identify the level of application of the governance principles in Yemeni universities from the point of view of faculty members and academic leaders. The research followed the descriptive / analytical method, and the questionnaire was used as a research tool. The sample consisted of (94) academic leaders and faculty members of the Universities of Sana'a and Science and Technology: (36) participants from Sana’a and (58) from Science and Technology. The results showed that the sample’s degree of assessment of the level of application of governance principles at Sana'a University was low with an average of (2.1056); the dimension of fairness came first and the dimension of participation received the last rank. Further, the sample’s assessment degree of the level of application of the governance principles at the University of Science and Technology was high with an average of (3.8198); the dimension of responsibility received the first rank, and the dimension of participation received the last rank. There were statistically significant differences between the average scores of the sample members in favor of the University of Science and Technology in all areas of governance. The study recommended that government universities should strive to implement the governance principles in order to increase their efficiency, effectiveness, competitiveness and quality of services. Also, private universities should strive to apply the governance principles to ensure their continuity, competitiveness and quality.